Dichlorido(N,N-diethyl-4-{[(quinolin-2-yl)methylidene]amino-κ(2) N,N′}aniline)mercury(II) - Faizi, Md. Serajul Haque (International Union of Crystallography, 2014)
In the mononuclear title complex, [HgCl(2)(C(20)H(21)N(3))], synthesized from the quinoline-derived Schiff base N (1),N (1)-diethyl-N (4)-(quinolin-2-ylmethylidene)benzene-1,4-diamine (QMBD), the coordination geometry around the Hg(2+) atom is distorted tetrahedral, comprising two Cl atoms [Hg—Cl = 2.3654 (19) and 2.4394 (18) Å] and two N-atom donors from the QMBD ligand, viz. one imine and quinoline [Hg—N = 2.334 (5) and 2.340 (5) Å, respectively]. In the crystal, weak C—H⋯Cl hydrogen bonds and weak π–π aromatic ring stacking interactions [minimum ring-centroid separation = 3.680 (4) Å] give an overall three-dimensional network.